2007
DOI: 10.1080/09723757.2007.11886004
|View full text |Cite
|
Sign up to set email alerts
|

Study of DYS 390 Polymorphism among Khatri Population of Punjab in Comparison to Other Indian and World Population

Abstract: The Y chromosome specific polymorphism (Y-STR and Y-SNPs) can be used to track paternal lineages as well as male specific movements and admixture among humans. The objective of the present work is to study the genetic polymorphism at Y chromosome specific STR locus, DYS390 among Khatri population of Punjab and generate a comparative data with respect to other Indian and world populations. The DNA was isolated from blood samples of Khatri male individuals through organic method and were amplified by PCR using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…A very few number of genetic studies (Badaruddoza et al 2007(Badaruddoza et al , 2008Badaruddoza and Sudhir 2012;Saini et al 2012) have been carried out on Punjabi population. However, no STR marker based study on present study populations have been reported in the literature till date.…”
Section: Population Informationmentioning
confidence: 99%
“…A very few number of genetic studies (Badaruddoza et al 2007(Badaruddoza et al , 2008Badaruddoza and Sudhir 2012;Saini et al 2012) have been carried out on Punjabi population. However, no STR marker based study on present study populations have been reported in the literature till date.…”
Section: Population Informationmentioning
confidence: 99%